Examining the relationship of paternalistic leadership, extent of centralisation and employee's voice behaviour. (31st March 2023) - Mumtaz, Bushra; Azhar, Aisha; Abdullah, Muhammad Ibrahim; Khan, Afshan Azam
Among many leadership approaches in Asia, literatures failed to gauge applicability of paternalistic leadership in Pakistani organisations. This research stresses on discussing how voice varies across the triad model of paternalistic leadership styles, power distance orientation, their interactions, and extent of centralisation. Data was collected from a sample of 324 employees, which includes 146 employees from public and 178 employees from private universities and banks. The proposed hypotheses were tested by using confirmatory factor analysis followed by multiple regression analysis. The findings showed that employees' voice behaviour was negatively associated with authoritarian paternalism; positively associated with benevolent and moral paternalism; and negatively associated with extent of centralisation. Also, the positive relationship of benevolent paternalism and employees' voice behaviour was stronger when employees experience high levels of power distance, thereby accepting the proposed hypotheses. However, contrary to the propositions, no significant results were obtained regarding power distance moderating negative authoritarian and positive moral paternalist link with voice behaviour. Implications of findings and future research prospects are discussed.